2019
DOI: 10.1021/acs.jpca.9b02298
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations on Relaxed Reduced-Dimensional Potential Energy Surfaces

Abstract: Molecular dynamics (MD) simulations with full-dimensional potential energy surfaces (PESs) obtained from high-level ab initio calculations are frequently used to model reaction dynamics of small molecules (i.e., molecules with up to 10 atoms). Construction of full-dimensional PESs for larger molecules is, however, not feasible since the number of ab initio calculations required grows rapidly with the increase of dimension. Only a small number of coordinates are often essential for describing the reactivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 95 publications
0
23
0
Order By: Relevance
“…For example, a recent paper by Liu et al details a method of using RDPESs on which to conduct ab initio molecular dynamics (MD) simulations where the RDPESs were constructed using geometric coordinates "chosen based on the chemical knowledge of the system." 2 In addition to generating RDPESs, similar approaches (e.g., choosing specic bond distances, angles, and dihedrals along the course of trajectories as in ref. [3][4][5][6][7][8] are oen used to plot several MD trajectories, and to carry out free energy sampling [e.g., using methods like umbrella sampling, 9 metadynamics, 10 boxed molecular dynamics (BXD), 11,12 forward ux sampling, 13 milestoning, 14 all of which require a well-dened reduced dimensional space of collective variables from which to sample].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent paper by Liu et al details a method of using RDPESs on which to conduct ab initio molecular dynamics (MD) simulations where the RDPESs were constructed using geometric coordinates "chosen based on the chemical knowledge of the system." 2 In addition to generating RDPESs, similar approaches (e.g., choosing specic bond distances, angles, and dihedrals along the course of trajectories as in ref. [3][4][5][6][7][8] are oen used to plot several MD trajectories, and to carry out free energy sampling [e.g., using methods like umbrella sampling, 9 metadynamics, 10 boxed molecular dynamics (BXD), 11,12 forward ux sampling, 13 milestoning, 14 all of which require a well-dened reduced dimensional space of collective variables from which to sample].…”
Section: Introductionmentioning
confidence: 99%
“…The lowest potential energy of molecular dynamic simulation indicates that the molecular system is entirely relaxed and unstrained. This means that all bonds, angles, and torsions are at their "natural" values according to the input force field parameters (Liu et al, 2019). In this study, we performed a molecular dynamics simulation with iso-thermal and isobaric conditions.…”
Section: Molecular Dynamics Resultsmentioning
confidence: 99%
“…Sparse polynomial interpolation with the Clenshaw−Curtis nodes has been used for PES approximation in the context of cis−trans isomerization (d ≤ 6, N data ≤ 4865), 54 intersystem crossing (d = 3, N data = 69), 55 and molecular dynamics of NH 3 inversion (d = 3, N data = 441; d = 6, N data = 4865). 56 In the NH 3 study, the number of nodes was chosen to interpolate Cartesian geometries, in addition to the PES, accurately. Morrow et al showed that sparse trigonometric interpolation (Figure 1; d = 2, N data = 136) accurately reproduces the periodicity of the PES gradient and can even result in better approximation than polynomial interpolation with a similar number of nodes.…”
Section: Interpolative Methodsmentioning
confidence: 99%